Electrochemical CO2 Reduction: A Classification Problem. Issue 22 (19th October 2017) - Bagger, Alexander; Ju, Wen; Varela, Ana Sofia; Strasser, Peter; Rossmeisl, Jan
Abstract: In this work, we propose four non‐coupled binding energies of intermediates as descriptors, or "genes", for predicting the product distribution in CO2 electroreduction. Simple reactions can be understood by the Sabatier principle (catalytic activity vs. one descriptor), while more complex reactions tend to give multiple very different products and consequently the product selectivity is a more complex property to understand. We approach this, as a logistical classification problem, by grouping metals according to their major experimental product from CO2 electroreduction: H2, CO, formic acid and beyond CO* (hydrocarbons or alcohols). We compare the groups in terms of multiple binding energies of intermediates calculated by density functional theory. Here, we find three descriptors to explain the grouping: the adsorption energies of H*, COOH*, and CO*. To further classify products beyond CO*, we carry out formaldehyde experiments on Cu, Ag, and Au and combine these results with the literature to group and differentiate alcohol or hydrocarbon products. We find that the oxygen binding (adsorption energy of CH3 O*) is an additional descriptor to explain the alcohol formation in reduction processes. Finally, the adsorption energy of the four intermediates, H*, COOH*, CO*, and CH3 O*, can be used to differentiate, group, and explain products in electrochemical reduction processes involving CO2, CO, and carbon–oxygen compounds. Abstract : CO2 reduction : A product classification of metal catalysts for the electroreduction of CO2 is shown in a periodic table with colors and compared with the three‐dimensional space for the proposed descriptors towards H2, CO, and HCOOH (formic acid). The color representation in the three‐dimensional plot allows one to group and classify each major product with descriptors.